Politik Strategis Berbasis Internet pada Akun Facebook Komunitas Petani Indonesia - Ahmad Badari Burhan (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2019)
This research is intended to review the use of Facebook by Indonesian farmer community in the strategic political platform. This issue is important to formulate as participatory communication stresses the importance of dialogue and rejects strategic communication efforts. If the community's active involvement in normative social change is desirable and pragmatically important to produce sustainable change, it is necessary to discuss how communication, strategy, and participation are interrelated. The results of this study indicate that the use of Facebook as a social networked site by the Indonesian farmer community is still dominated by information sharing and knowledge of cultivation and trading, as well as a medium for social interaction. Strategic political discourse occasionally and weakly appears related to government policies that are considered to be inadequate to farmers, among others related to rice import policy during the harvest, and the lack of government attention when their crops are faced with price declines, while production costs are steadily increasing. Penelitian ini dimaksudkan untuk meninjau penggunaan media sosial Facebook oleh komunitas petani Indonesia dalam platform politik strategis. Permasalahan ini penting untuk dirumuskan karena komunikasi partisipatoris menekankan pentingnya dialog dan menolak upaya-upaya komunikasi strategis. Jika keterlibatan aktif masyarakat dalam perubahan sosial secara normatif diinginkan dan secara pragmatis penting untuk menghasilkan perubahan yang berkelanjutan, perlu untuk membahas bagaimana komunikasi, strategi, dan partisipasi saling terkait. Hasil penelitian ini menunjukkan bahwa penggunaan Facebook sebagai situs sosial berjaringan oleh komunitas petani Indonesia masih didominasi oleh sharing informasi dan pengetahuan budidaya dan tata niaga, di samping sebagai media untuk interaksi sosial. Wacana politik strategis muncul sekali-sekali terkait dengan kebijakan pemerintah yang dianggap kurang berpihak kepada petani, antara lain terkait dengan kebijakan impor beras saat panen raya, dan kurangnya perhatian pemerintah manakala hasil panen mereka dihadapkan pada penurunan harga, sementara biaya produksi diwacanakan semakin mahal. This research is intended to review the use of Facebook by Indonesian farmer community in the strategic political platform. This issue is important to formulate as participatory communication stresses the importance of dialogue and rejects strategic communication efforts. If the community's active involvement in normative social change is desirable and pragmatically important to produce sustainable change, it is necessary to discuss how communication, strategy, and participation are interrelated. The results of this study indicate that the use of Facebook as a social networked site by the Indonesian farmer community is still dominated by information sharing and knowledge of cultivation and trading, as well as a medium for social interaction. Strategic political discourse occasionally and weakly appears related to government policies that are considered to be inadequate to farmers, among others related to rice import policy during the harvest, and the lack of government attention when their crops are faced with price declines, while production costs are steadily increasing.